2014
DOI: 10.3109/00365513.2014.921835
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine-induced cutaneous reactions: A simple assay to identify patients carrying the HLA-A*31:01 allele

Abstract: We have designed and validated a simple, fast and inexpensive test for the rs1061235A> T SNP as a marker for HLA-A*31:01 in the Norwegian population for potential use in a personalized treatment approach to patients planned to receive CBZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Across all ancestral groups in which rs1061235 was identified, the r 2 value was 1.000. Thorstensen et al (2014) used a polymerase chain reaction-restriction fragment length polymorphism assay to investigate rs1061235 as a tag for HLA-A*31:01 in Norwegians. In a set of 204 samples, their assay had 100% sensitivity and 99.5% specificity for tagging HLA-A*31:01 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all ancestral groups in which rs1061235 was identified, the r 2 value was 1.000. Thorstensen et al (2014) used a polymerase chain reaction-restriction fragment length polymorphism assay to investigate rs1061235 as a tag for HLA-A*31:01 in Norwegians. In a set of 204 samples, their assay had 100% sensitivity and 99.5% specificity for tagging HLA-A*31:01 .…”
Section: Resultsmentioning
confidence: 99%
“…The assay performs best when the number of PCR amplification cycles is increased to 50 (increasing total run time from 90 to 110 min). Assay ANNK49J for rs1061235 also identified HLA-A*31:01 with 100% sensitivity, with its specificity impacted by this SNV also being present in the HLA-A*33:01 and HLA-A*33:03 haplotypes ( Thorstensen et al, 2014 ). A study in an ancestrally-diverse group of Canadian children ( Amstutz et al, 2013 ) found that out of 20 children carrying the minor allele of rs1061235, 12 had a haplotype of HLA-A*31:01 , five had a haplotype of HLA-A*33:03 , and three had a haplotype of HLA-A*33:01 .…”
Section: Discussionmentioning
confidence: 99%
“…High risk of a false positive result by cross-contamination during the second PCR.PCR-RFLPrs1061235 linked to HLA-B*31:01Thorstensen et al. 2014 77 RapidCheapThe method has be applied in certain populations (the Norwegian population). For other populations, validation is needed.…”
Section: Hla and Hla Typing Methods For Hla Screeningmentioning
confidence: 99%
“…It is, however, a potential candidate for utilization in HLA screening due to its simplicity and cost-effectiveness 74 . Currently, there are a number of single nucleotide polymorphisms (SNPs) which have been reported as potential surrogate markers, based on their linkage disequilibrium (LD) for detection of HLA-B*15:02, 75 HLA-B*58:01 76 and HLA-A*31:01, 77 HLA-B*57:0178, 79 Heterogeneity has been observed, however, across different populations 80 . For example, a haplotype of two SNPs, rs2844682C ​> ​T and rs3903184C ​> ​G, was proposed as a surrogate marker for HLA-B*15:02 in Han Chinese, 75 although later work refuted this finding 81 , and rs9263726 A ​> ​G has been found to be tightly linked with HLA-B*58:01 in Japanese 15 and Chinese 82 but not Australians 83 .…”
Section: Hla and Hla Typing Methods For Hla Screeningmentioning
confidence: 99%
“…However, the recent assays proposed for the screening test are only able to detect the HLA‐B*15:02 allele or the HLA‐A*31:01 allele, separately. Consequently, this can raise the cost and time requirement for performing the screening test.…”
Section: Introductionmentioning
confidence: 99%